Carboxy-terminal fragment of amyloid precursor protein mediates lipid droplet accumulation upon γ-secretase inhibition - Oikawa, Naoto; Fabiano, Marietta; Müller, Ulrike C.; Walter, Jochen (Biochemical and biophysical research communications, 2021)
γ-Secretase is a protease catalysing the proteolysis of type-I membrane proteins usually after precedent ectodomain shedding of the respective protein substrates. Since proteolysis of membrane proteins is involved in fundamental cellular signaling pathways, dysfunction of γ-secretase can have significant impact on cellular metabolism and differentiation. Here, we examined the role of γ-secretase in cellular lipid metabolism using neuronally differentiated human SH-SY5Y cells. The pharmacological inhibition of γ-secretase induced lipid droplet (LD) accumulation. The LD accumulation was significantly attenuated by preventing the accumulation of C-terminal fragment of the amyloid precursor protein (APP-CTF), which is a direct substrate of γ-secretase. Additionally, LD accumulation upon γ-secretase inhibition was not induced in APP-knock out (APP-KO) mouse embryonic fibroblasts (MEFs), suggesting significant involvement of APP-CTF accumulation in LD accumulation upon γ-secretase inhibition. On the other hand, γ-secretase inhibition-dependent cholesterol accumulation was not attenuated by inhibition of APP-CTF accumulation in the differentiated SH-SY5Y cells nor in APP-KO MEFs. These results suggest that γ-secretase inhibition can induce accumulation of LD and cholesterol differentially via APP-CTF accumulation.